1997
DOI: 10.1111/j.1600-0528.1997.tb01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Insurance status and provision of dental services in Australian private general practice

Abstract: Annual expenditure on dental care in Australia amounts to AUD 1.9 billion. Approximately one-third of this expenditure involves private dental insurance, yet little is known about the impact of insurance on the provision of services. The aim of this analysis was to examine differences in dental service provision between insured and non-insured patients. Data collected from a random sample of dentists from a survey conducted in 1993-94 were used, providing 817 responses (response rate 74%). Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
(13 reference statements)
2
29
0
Order By: Relevance
“…Insured adults receive more preventive care and fewer extractions. 11,13 Despite these considerations, there was no variation in total expenditure by dental insurance status. However, having insurance was strongly associated with lower out-of-pocket expenditure.…”
Section: Discussion Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insured adults receive more preventive care and fewer extractions. 11,13 Despite these considerations, there was no variation in total expenditure by dental insurance status. However, having insurance was strongly associated with lower out-of-pocket expenditure.…”
Section: Discussion Key Findingsmentioning
confidence: 99%
“…9 Another study, also of older adults, found that out-ofpocket costs were positively associated with being uninsured for dental care, higher family income, having a high school or college degree, having poor or fair self-reported general health and with being edentulous. 10 Variations in dental attendance and types of services received by insurance status have been well reported; [11][12][13] however, it is not known whether the total costs associated with care also differ by insurance status. Deriving current estimates of expenditure for uninsured populations are necessary for informing policy.…”
Section: Introductionmentioning
confidence: 99%
“…32 Patients with dental insurance have been reported to be more likely to receive preventive, crown and bridge and endodontic services, but less likely to receive extractions and with no differences in receipt of diagnostic, restorative or prosthodontic services. 33 For low socioeconomic groups having dental insurance was associated with better self-rated dental health.…”
Section: Accepted Articlementioning
confidence: 98%
“…The questions in this interview were based on related studies,14,18,25,26 and after the pilot study were slightly modified. The questionnaire covered respondents’ insurance status, characteristics of dental attendance, and socio-demographic information.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to insurance status, other receiver-based factors should be taken into account. These include demographic factors,14 socioeconomic status,11 dental conditions,12 reason for visit, and attitudes towards health care 13…”
Section: Introductionmentioning
confidence: 99%